Castleman disease in salivary gland: report of a pediatric case - García Pita, Elián; Salazar, Andrea; Ruggeri, Carlos S. (Revista del Hospital Italiano de Buenos Aires, 2015)
Castleman disease (CD) is a rare lymphoproliferative entity characterized for a non – neoplasic progressive growth of the lymph nodes in any part of the body; nevertheless it usually affects the mediastinum (60 %), and with less frequency, it compromises the head and neck region, including the salivary glands. It represents a diagnostic challenge for the doctor, because it has nonspecific symptoms and signs. There are two subtypes: the localized form, that generally is presented through an adenopaty without systemic symptoms, and a multicentric form that compromises several nodal groups and has systemic symptoms and laboratory abnormalities. Diagnosis requires a complete physical examination and complementary exams (blood tests, ultrasonography, computed tomography and/or magnetic resonance, fine needle puncture – aspiration), and the final diagnosis is through histopathological analysis. The treatment is surgery, but multicentric form requires adyuvant treatment. Although its unusual presentation in salivary glands, CD should be considered between differential diagnosis, especially when we are thinking of lymphoproliferative entities. In this article, we present a case of a pediatric patient with diagnosis of CD of submaxilar gland and we review the literatura about this disease with special attention in the salivary glands location
Keywords: Castleman disease; salivary glands tumors